Down's syndrome and education : how access to schools affect membership in society - Lim, Khairul Anwar Abdul Hadi (2015)
Special needs individuals face different kinds of struggles in their everyday lives. The impact education system has on Down’s Syndrome individuals is an area that has not yet been studied. The institution of education is a crucial site to understand how it affects their quality of life. Based on in-depth interviews and some ethnographic work with parents and teachers, this paper finds that because of the interplay between impairment and society, the more resources a Down’s Syndrome individual receives from parents and schools, the higher the likelihood that he or she will be accepted into employment and gain membership in capitalistic societies with neoliberal economies. Finally, through the research process, this paper finds recommendations, the most imminent being investing on state welfare for its own citizens – special needs individuals.